Students' Perceptions in The Utilization of Zoom Video Conferencing on Speaking Ability in Distance Learning - Nita Kaniadewi (Yayasan Visi Intan Permata, 2022)
This research examined students’ perception of the use of Zoom Video Conferencing in successful speaking ability during the COVID-19 outbreak. This research aimed to obtain valid evidence about EFL college students’ own decent or wicked perception of the utilization of Zoom Video Conferencing for sharpening their speaking competencies. The researcher used mix methods approach convergent design with a combination between a quantitative approach and a qualitative approach. In assembling the data, the researcher involved university students in some different majors with 102 participants gathered by sharing the close-ended and open-ended questionnaires in the form of Google Forms in the research. The researcher analyzed the data from close-ended questionnaire results and open-ended questionnaire responses. The results showed that the close-ended questionnaire discovered good perceptions and positive attitudes of students in increasing speaking skills towards Zoom Video Conferencing. Therefore, Zoom Video Conferencing can be a medium in teaching activity during distance learning applications especially in improving speaking ability as it can raise students’ positive attitude and speaking ability in EFL classrooms.